The Impact of Digitalization on the Optimization of Zakat Fund Collection at Baznas Republic of Indonesia - Jumratul Aini; Muh. Yunan Putra; Dinah Husniah (FiTUA: JURNAL STUDI ISLAM, 2025)
This study aims to analyze the effect of digitalization on optimizing the receipt and distribution of zakat funds at the National Amil Zakat Agency (BAZNAS) Indonesia. The background of this research is based on the polemics over the free lunch program which raises the discourse on the utilization of zakat, infaq, and sadaqah (ZIS) funds, as well as the importance of transparent, targeted, and sharia-compliant ZIS fund management. Digitalization is seen as a strategic solution in improving the efficiency and accountability of ZIS fund management. This study uses a quantitative approach with a secondary data analysis method from the financial and operational reports of the central BAZNAS and 26 provincial BAZNAS during the period 2022-2024. Data were obtained through documentation, exploration of the BAZNAS Information Management System (SiMBA) database, and study of related literature. Preliminary results show that the application of digital technologies such as e-wallet, marketplace, SIMZIS, and artificial intelligence has increased the number of muzakki, accelerated fund distribution, and strengthened transparency. However, challenges such as limited digital infrastructure and low technological literacy are still major obstacles. This research is expected to provide strategic recommendations for the development of more inclusive and effective digitalization of zakat institutions in Indonesia.